El Programa Nacional de Referencia de Biobanco Genómico de la Población Argentina (PoblAr): una crítica a su fundamentación ética = The National Genomic Biobanco Reference Program of the Argentine population (Populate) : a criticism of its ethical foundation - Pallitto, Nahuel; Delvitto, Ailin; Petino Zappala, María Alejandra; Lavagnino, Nicolás José; Mallou, Carolina Ocampo (Salud, ciencia y tecnología. Serie de conferencias, 2023)
The scientific and technological research that involves human beings require for their approval and implementation of an ethical analysis that interrogates about the goodness, correction or desirability of its implementation. In Argentina, ethical evaluations are carried out by the so -called "Ethics Committees in Research", spaces mostly formed by experts and experts from various thematic areas, with little or no participation of the communities involved that are recipients of research . With this ethical evaluation methodology, the National Genomic Biobanco Reference Program of the Argentine Population (Popular) was launched in recent years, whose goal is to obtain genomic, phenotypic and lifestyles of life from different communities of the territory of the territory of the territory Argentine to offer personalized diagnoses and treatments. The main objective of this work is to make a criticism of the ethical foundation of the popular, at the same time exhibiting the limitations of the paradigm of ethics in hegemonic research that is at the basis of all institutionalized ethical evaluations. To do this, we will resort to two alternative ethical paradigms of different origin and with various budgets: responsible research and innovation and Latin American critical ethics. With their differences, both perspectives allow to glimpse that the popular suffers from an adequate ethical foundation and that, therefore, was promoted and executed under morally problematic conditions.